2005
DOI: 10.21273/horttech.15.3.0535
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Weed Control Practices in Container Nurseries

Abstract: Container production has increased rapidly in many parts of the U.S. over the past 15 years. Container production has been the fastest growing sector in the nursery industry and the growth is expected to continue. Weed growth in container-grown nursery stock is a particularly serious problem, because the nutrients, air, and water available are limited to the volume of the container. The extent of damage caused by weeds is often underestimated and effective control is essential. Various researchers have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
63
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 38 publications
0
63
0
3
Order By: Relevance
“…As profit margins decline and the input costs continually increase, researchers and nursery growers have looked for ways to decrease production costs. From a weed control perspective, this would include many different preventative and sanitation measures, as well as chemical and nonchemical methods of weed control to improve crop growth, reduce economic burden, and increase product marketability (Case et al, 2005;Fausey, 2003).…”
Section: Introduction To Current Weed Control Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As profit margins decline and the input costs continually increase, researchers and nursery growers have looked for ways to decrease production costs. From a weed control perspective, this would include many different preventative and sanitation measures, as well as chemical and nonchemical methods of weed control to improve crop growth, reduce economic burden, and increase product marketability (Case et al, 2005;Fausey, 2003).…”
Section: Introduction To Current Weed Control Methodsmentioning
confidence: 99%
“…This is no longer the case as labor costs continue to increase and labor availability decreases. Mathers (2003) reported that nurseries may spend as much as $9900 per ha on the manual removal of weeds, and economic losses due to weed infestations have been estimated at $17,300 per ha (Case et al, 2005). Similarly, Darden and Neal (1999) reported a cost of $1367 to hand weed 1000 3-L pots over a 4-month period.…”
Section: Introduction To Current Weed Control Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research focusing on metolachlor has shown that it is tightly bound to organic substrates (Grey et al, 1996;Koncal et al, 1981;Mahnken et al, 1994). One of the most common preemergence herbicides in nursery production, oxyfluorfen, has been shown to be more mobile in pine bark than peat; however, it was largely immobile in both substrates (Case et al, 2005;Horowitz and Elmore, 1991). A study conducted by Simmons and Derr (2007) demonstrated that there was greater pendimethalin leaching in pine bark compared with a Tetotum fine loam field soil.…”
mentioning
confidence: 99%